Study on the effect of microalgae – bacteria growth conditions in synthetic wastewater treatment - Samsudin, Amirah; Abdul Halim, Amanatuzzakiah; Azmi, Azlin Suhaida; Mohd Nawi, Nazri Mohd (2022)
Microalgae has been widely used for wastewater treatment as wastewater contains nutrients that are essential for microalgal growth. In addition, the co-culture system of microalgae-bacteria was reported to be able to improve the efficiency of wastewater treatment compared to microalgae alone. Bacteria help microalgae break down the complex nutrients present in wastewater into simpler compounds, which will be easily assimilated by microalgae. However, to achieve high nutrients (ammonium and phosphorus) and COD removals in wastewater treatment, the best growth conditions of both microbes need to be investigated. The objective of this study is to investigate how the selected factors affect the removal of nutrients and COD at particular ranges through One-Factor-at-a-Time (OFAT) method. We successfully evaluated the effects of three significant growth conditions, namely the initial concentration of microalgae, initial concentration of bacteria, and inoculation time of bacteria on the removal of nutrients and COD in synthetic wastewater. The highest nutrients and COD removal were achieved when the initial concentration of microalgae and bacteria was at 0.77 g/L and 104 CFU/mL, respectively, and the best time to inoculate bacteria was at day 1.52. Moreover, models for all three factors were validated and verified using ANOVA, with percentage error of predicted values and experimental values was less than 10%. Hence, these conditions can be used as the basis for further optimization process in order to improve the wastewater treatment by microalgae-bacteria co-culture system.